Pre-extension demonstration of field pea varieties in selected districts of Bale highlands, Oromiya national regional state, Ethiopia (Research in Agriculture Livestock and Fisheries, 2022)
Pre extension demonstration of improved field pea varieties was conducted in Goba, Sinana and Agarfa districts of Bale zone. The main objective of the study was to demonstrate and evaluate recently released (Weyib) variety along with standard check. The demonstration was under taken on single plot of 10mx10m area for each variety with the spacing of 30cm between rows and recommended seed rate of 75kg/ha and fertilizer rate of 100kg/ha NPS. Mini-field day involving different stakeholders was organized at each respective site. Yield data per plot was recorded and analysed using descriptive statistics, while farmers’ preference to the demonstrated varieties was identified using focused group discussion and summarized using pair wise ranking methods. The demonstration result revealed that Weyib variety performed better than the standard check (Tulu shanan variety) with an average yield of 34.47qt/ha, while that of the standard check was27.26qt/ha. Weyib variety had 17.27% yield advantage over the standard check. Thus, Weyib variety was recommended for further scaling up.Res. Agric., Livest. Fish.8(3): 267-271, December 2021